Coupled Fixed Point Theorems in Soft Metric Space. (2020) - Raghunath Wadkar, Balaji; Bhardwaj, Ramakant; Mohan Sharaff, Rakesh
Abstract: This paper contains the coupled soft fixed theorems with themonotone and alpha monotone rule in soft metric space